2021
DOI: 10.1016/j.jcot.2020.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of percutaneous trigger finger release technique using a 20-gauge hypodermic needle

Abstract: Background: Trigger finger or stenosing tenosynovitis is a disproportion between the volume of the tendon sheath and its contents. This disproportion prevents gliding of the tendon as it moves freely through the annular pulley. The technique of percutaneous release of the annular pulley for trigger finger has been described well in the literature, which has undergone several modifications, like use of hypodermic needle, tenotome or specially designed knives. Method: We performed percutaneous trigger finger rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
7
2
1
Order By: Relevance
“…Release of the pulley is assessed by loss of a grating sensation along the pulley and by having the patient actively range the finger. 15 OPEN RELEASE Open surgical trigger finger release remains the most effective treatment modality, with success rates nearing 100%. 16 Patients with a long duration of preoperative symptoms, flexion contracture of the PIP joint, and fraying or partial tear of the flexor tendon may be at increased risk of prolonged symptoms such as pain, reduced range of motion, catching and locking, among others despite surgical release.…”
Section: Operative Managementmentioning
confidence: 99%
“…Release of the pulley is assessed by loss of a grating sensation along the pulley and by having the patient actively range the finger. 15 OPEN RELEASE Open surgical trigger finger release remains the most effective treatment modality, with success rates nearing 100%. 16 Patients with a long duration of preoperative symptoms, flexion contracture of the PIP joint, and fraying or partial tear of the flexor tendon may be at increased risk of prolonged symptoms such as pain, reduced range of motion, catching and locking, among others despite surgical release.…”
Section: Operative Managementmentioning
confidence: 99%
“…The prolonged inflammation leads to a swelling of the tendon sheath at the intersection with the pulley (usually in the A1 pulley), preventing the tendon from sliding smoothly through the channel during movements of flexion and extension. 1 Its clinical manifestation can vary from an occasional blockage to complete entrapment of the tendon in flexion, sometimes occurring even in extension. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous trigger digit release has the advantage of giving similar results to open release and has fewer complications (Gilberts et al., 2001; Wang et al., 2013). Many studies have reported a success rate of over 90% for percutaneous A1 pulley release (Bamroongshawgasame, 2010; Blumberg et al., 2001; Panghate et al., 2021; Rojo-Manaute et al., 2012). After pulley release, steroid injection can be administered to treat postoperative pain and swelling (Jegal et al., 2019; Levine et al., 2022).…”
Section: Introductionmentioning
confidence: 99%